Enhanced MRI and MRI-Guided Interventional Procedures in Women with Asymptomatic Silicone-Injected Breasts. (12th March 2012) - Cheung, Yun-Chung; Chen, Shin-Chih; Lo, Yung-Feng
Abstract : Asymptomatic women who have received silicone injection for breast augmentation have a risk of underestimating breast cancer by palpation, mammography, or breast sonography. Enhanced breast MRI is sensitive to display certain nonspecific enhanced lesions or suspicious lesions. Such nonspecific MRI-detected lesions could be managed by American College Radiology BI-RADS lexicon and selectively with MRI-guided techniques biopsy to prevent unnecessary surgery.